Relationship between the nutrition status, level of depression and food satisfaction of home care users - Afonso, Cláudia (2016)
The aim of this study was to evaluate the nutritional status of home care users (SAD) of a servissefrom a northern area, as well as their satisfaction with the food service provided, taking into accountsocial and level of depression conditions.We conducted an observational descriptive study of cross-sectional design. The sample wascomposed of 54 users SAD, constituting 51% of the population who enjoys the service, to which wasapplied: 1) the Mini Nutritional Assessement (MNA); 2) structured questionnaire of indirect application,with single or multiple answer questions, to collect socio-demographic information and assessmentof satisfaction with the food service; 3) Geriatric Depression Scale Short Form (GDS-15).Data analysis revealed a percentage of malnourished users of 31.5% and a statistically significantassociation between nutritional status and level of depression. Most respondents expressedsatisfaction with the meals served by the institution. Malnourished users had a lower level ofsatisfaction although this difference was not statistically significant.The present research results highlight the urgent need to assess and monitor the nutritional statusalong with the level of depression, in order to define effective and practical intervention strategies toimprove the quality of life in this population.